Host-Specific Enzyme-Substrate Interactions in SPM-1 Metallo-beta-Lactamase are Modulated by Second Sphere Residues - Gonzalez, Lisandro Javier (2014)
Pseudomonas aeruginosa is one of the most virulent and resistant non-fermenting Gram-negative pathogens in the clinic. Unfortunately, P. aeruginosa has acquired genes encoding metallo-beta-lactamases (MBLs), enzymes able to hydrolyze most beta-lactam antibiotics. SPM-1 is an MBL produced only by P. aeruginosa, while other MBLs are found in different bacteria. Despite similar active sites, the resistance profile of MBLs towards beta-lactams changes from one enzyme to the other. SPM-1 is unique among pathogen-associated MBLs in that in that it contains "atypical" second sphere residues (S84, G121). Codon randomization on these positions and further selection of resistance-conferring mutants was performed. MICs, periplasmic enzymatic activity, Zn(II) requirements, and protein stability was assessed. Our results indicated that identity of second sphere residues modulates the substrate preferences and the resistance profile of SPM-1 expressed in P. aeruginosa. The second sphere residues found in wild type SPM-1 give rise to a substrate selectivity that is observed only in the periplasmic environment. These residues also allow SPM-1 to confer resistance in P. aeruginosa under Zn(II)-limiting conditions, such as those expected under infection. By optimizing the catalytic efficiency towards beta-lactam antibiotics, the enzyme stability and the Zn(II) binding features, molecular evolution meets the specific needs of a pathogenic bacterial host by means of substitutions outside the active site.